2011
DOI: 10.1016/j.physa.2011.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heterogeneous human activities on epidemic spreading

Abstract: Recent empirical observations suggest a heterogeneous nature of human activities. The heavy-tailed inter-event time distribution at population level is well accepted, while whether the individual acts in a heterogeneous way is still under debate. Motivated by the impact of temporal heterogeneity of human activities on epidemic spreading, this paper studies the susceptible-infected model on a fully mixed population, where each individual acts in a completely homogeneous way but different individuals have differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…This effect, which we call population effect, is also observed in Fig. 4 of [8] where the authors study the impact of heterogeneous human activities on epidemic spreading through simulations. Theorem 3 also says that the degree of acceleration is asymptotically proportional to the network size.…”
Section: Theoremsupporting
confidence: 60%
See 1 more Smart Citation
“…This effect, which we call population effect, is also observed in Fig. 4 of [8] where the authors study the impact of heterogeneous human activities on epidemic spreading through simulations. Theorem 3 also says that the degree of acceleration is asymptotically proportional to the network size.…”
Section: Theoremsupporting
confidence: 60%
“…The authors in [7] derived a closed-form equation for the critical level of virus infection rate that lets a virus persist in a network when the virus is recoverable with a certain rate. More realistic average spread behaviors of a virus with the heterogeneity inherent in human mobility patterns have been studied through simulations in [8]. In computer networks, [9] analyzed the average propagation behavior of code red worm in the Internet using measurement data from ISPs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to imperfect mixing in space, it has recently been shown that imperfect mixing in time also causes slowerthan-expected transmission over time-ordered networks [44,51]. [52,53].…”
Section: Temporal Activity Patterns Enable Transmission Dualitymentioning
confidence: 99%
“…[39,40] with weights between w min = 1 and w max = 10 4 . The former has a clear mean, while the latter lacks a characteristic mean.…”
Section: Modelmentioning
confidence: 99%